Canagliflozin: a sodium glucose co‐transporter 2 inhibitor for the treatment of type 2 diabetes mellitus. Issue 1 (25th August 2015) - Rosenthal, Norm; Meininger, Gary; Ways, Kirk; Polidori, David; Desai, Mehul; Qiu, Rong; Alba, Maria; Vercruysse, Frank; Balis, Dainius; Shaw, Wayne; Edwards, Robert; Bull, Scott; et al.
Abstract : The sodium glucose co‐transporter 2 (SGLT2) inhibitor canagliflozin is a novel treatment option for adults with type 2 diabetes mellitus (T2DM). In patients with hyperglycemia, SGLT2 inhibition lowers plasma glucose levels by reducing the renal threshold for glucose (RTG ) and increasing urinary glucose excretion (UGE). Increased UGE is also associated with a mild osmotic diuresis and net caloric loss, which can lead to reductions in body weight and blood pressure (BP). After promising results from preclinical and phase I/II studies, the efficacy and safety of canagliflozin was evaluated in a comprehensive phase III development program in over 10, 000 patients with T2DM on various background therapies. Canagliflozin improved glycemic control and provided reductions in body weight and BP versus placebo and active comparators in studies of up to 2 years' duration. Canagliflozin was generally well tolerated, with higher incidences of adverse events (AEs) related to the mechanism of action, including genital mycotic infections and AEs related to osmotic diuresis. Results from the preclinical and clinical studies led canagliflozin to be the first‐in‐class SGLT2 inhibitor approved in the United States, and support canagliflozin as a safe and effective therapeutic option across a broad range of patients with T2DM.